1996
DOI: 10.1104/pp.111.4.1135
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of Class IV Chitinase in the Compatible Interaction of Bean Roots with Fusarium solani

Abstract: Three chitinase isoenzymes, PvChiE, PvChiF, and PvChiC (molecular masses 29, 28, and 27 kD, respectively), were purified from bean (Phaseolus vulgaris L. cv Saxa) roots infected with the funga1 pathogen Fusarium solani f. sp. phaseoli, and their amino acid sequence was partially determined. All sequences from all three isoenzymes exactly matched deduced amino acid sequences of the bean class IV chitinase PvChi4, formerly called PR4. The N terminus of PvChiF mapped to the hinge region, and the N terminus of PvC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 41 publications
0
28
0
2
Order By: Relevance
“…In vitro studies with Fusarium solani showed that both class I chitinase and class I β-1,3-glucanase are necessary to inhibit fungal growth (Mauch, Mauch-Mani & Boller, 1988 b ;SelaBuurlage et al, 1993), but upon prolonged exposure to these enzymes, the fungus was able to resume growth (Ludwig & Boller, 1990). In a recent study on the interactions of bean roots and soil-borne fungi, we provided evidence that class IV, and most likely also class I chitinase, are proteolytically cleaved by a protease that is induced in the compatible interaction of bean roots and Fusarium solani (Lange et al, 1996). Possibly, proteolytic processing of chitinase is part of the pathogen's strategy to inactivate the plant's defence.…”
Section: Compatibility and Plant Defencementioning
confidence: 99%
“…In vitro studies with Fusarium solani showed that both class I chitinase and class I β-1,3-glucanase are necessary to inhibit fungal growth (Mauch, Mauch-Mani & Boller, 1988 b ;SelaBuurlage et al, 1993), but upon prolonged exposure to these enzymes, the fungus was able to resume growth (Ludwig & Boller, 1990). In a recent study on the interactions of bean roots and soil-borne fungi, we provided evidence that class IV, and most likely also class I chitinase, are proteolytically cleaved by a protease that is induced in the compatible interaction of bean roots and Fusarium solani (Lange et al, 1996). Possibly, proteolytic processing of chitinase is part of the pathogen's strategy to inactivate the plant's defence.…”
Section: Compatibility and Plant Defencementioning
confidence: 99%
“…However, as fungi use multiple layers of defense against host chitinases, including masking chitin under a layer of b-glucans and other polysaccharides (Bowman and Free, 2006), converting chitin into chitosan (El Gueddari et al, 2002), secreting chitinase inhibitors (Lange et al, 1996), and possibly other chitin-binding effectors with a role in protection (for example, Ecp6 effectors are shown to partially protect against chitinases in some fungal species) (Marshall et al, 2011), a complete loss of pathogenicity in the DPf-Avr4 mutants was not observed and might also explain the differences in contribution to virulence between Pf-Avr4 and Cf-Avr4. Overall, our data indicate that Pf-Avr4 and Cf-Avr4 are true functional orthologs and physiologically relevant effectors for fungal infections in plants.…”
Section: Functional Conservation Within the Avr4 Effector Family Suggmentioning
confidence: 99%
“…For example, partial processing of pro-hevein results in the simultaneous occurrence of the precursor and its two domains in the latex of the rubber tree (Lee et al, 1991). Possibly, the processing of the chimeric precursors has a physiological meaning, as suggested by the observation that a class IV chitinase is proteolytically processed in bean roots in a compatible but not an incompatible interaction between bean and Fusarium solani (Lange et al, 1996).…”
Section: Discussionmentioning
confidence: 99%